Flow Cytometry Analysis of Blood Large Extracellular Vesicles in Patients with Multiple Sclerosis Experiencing Relapse of the Disease - Soukup, Jakub; Kostelanská, Marie; Kereïche, Sami; Hujacová, Andrea; Pavelcová, Miluše; Petrák, Jiří; Kubala Havrdová, Eva; Holada, Karel (Journal of clinical medicine, 2022)
The number of people living with multiple sclerosis (MS) in developed countries is increasing. The management of patients is hindered by the absence of reliable laboratory tests accurately reflecting the disease activity. Extracellular vesicles (EVs) of different cell origin were reportedly elevated in MS patients. We assessed the diagnostic potential, with flow cytometry analysis, of fresh large EVs (lEVs), which scattered more light than the 590 nm silica beads and were isolated from the blood plasma of relapsing remitting MS patients. Venous blood was collected from 15 patients and 16 healthy controls (HC). The lEVs were isolated from fresh platelet-free plasma by centrifugation, labelled with antibodies and the presence of platelet (CD41+, CD36+), endothelial (CD105+), erythrocyte (CD235a+), leukocyte (CD45+, CD19+, CD3+) and phosphatidylserine (Annexin V+) positive lEVs was analyzed using standard flow cytometry. Cryo-electron microscopy was used to verify the presence of EVs in the analyzed plasma fractions. MS patients experiencing acute relapse had slightly reduced relative levels (% of positive lEVs) of CD105+, CD45+, CD3+, CD45+CD3+ or CD19+ labelled lEVs in comparison to healthy controls. An analysis of other markers or a comparison of absolute lEV counts (count of lEVs/µL) did not yield any significant differences. Our data do not support the hypothesis that the exacerbation of the disease in RRMS patients leads to an increased numbers of circulating plasma lEVs which can be monitored by standard flow cytometry.
Keywords: extracellular vesicles; cryo-electron microscopy; plasma; flow cytometry; multiple sclerosis